Surgical Leadership - Peters, Walter; Picchioni, Anthony; Fleshman, James W. (Clinics in Colon and Rectal Surgery, 2020)
There are few topics of more importance in health care today than surgical leadership. The surgical leader will need to organize and maintain a collective effort if the organization is going to be effective. Health care teams work in a volatile, uncertain, complex, and ambiguous ecosystem. Therefore, surgeons must develop skills beyond the operating room. The facilitative leader will lead from the middle, not the top. They will empower coworkers to participate in creating a vision by building consensus, developing teams, clarifying roles, and earning the loyalty and trust of their colleagues. Surgical leaders will use communication as the vehicle for their success, including intentional listening, asking open-ended questions, and creating dialog instead of argumentative exchanges. The future of health care belongs to the physicians who are investing the time and effort today to become leaders.
Keywords: leadership; facilitate; teams